Energy consumption and energy efficiency in olive oil mills: case studies in Portugal and Spain in the frame of TESLA project - Baptista, F.J. (2016)
TESLA project (Transfering Energy Save Laid on Agroindustry) financed by the European Commission, had the main goals of evaluating the energy consumption and to identify the best available practices to improve energy efficiency in key agro-food sectors, such as the olive oil mills. A general analysis of energy consumptions allowed identifying the partition between electrical and thermal energy (approximately 50%) and the production processes responsible for the higher energy consumptions, as being the in the mill and paste preparation and the phases separation. Some measures for reducing energy waste and for improving energy efficiency were identified and the impact was evaluated by using the TESLA tool developed by Circe and available at the TESLA website.